2015
DOI: 10.1177/1077699015589187
|View full text |Cite
|
Sign up to set email alerts
|

Are Demographics Adequate Controls for Cell-Phone-Only Coverage Bias in Mass Communication Research?

Abstract: Cell-phone-only (CPO) households differ along key variables from non-CPO households, creating potential coverage biases in landline-only random-digit-dialing (RDD) surveys. Researchers have attempted to correct for this by weighting their data based on demographic differences. Previous research, however, has not examined CPO coverage biases in media-use surveys-an important oversight as cell phone use is itself a media choice. This article presents a secondary analysis of Pew's 2012 media consumption survey an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…stratified to be proportional to known population characteristics), if that is their objective. Researchers who choose to weight their responses to make up for under-and over-sampling should be expected to note the limitations of such procedures (see Watson et al, 2015).…”
Section: Recommendations For Reviewersmentioning
confidence: 99%
“…stratified to be proportional to known population characteristics), if that is their objective. Researchers who choose to weight their responses to make up for under-and over-sampling should be expected to note the limitations of such procedures (see Watson et al, 2015).…”
Section: Recommendations For Reviewersmentioning
confidence: 99%
“…The purpose of comparing the first two groups is to see how many differences there are in the two samples collected through different means to gauge the probable undercoverage issue. The rationale for adding the CO group for comparison purposes is because from the other studies carried out in US and Western countries (Keeter et al, 2007;Schneiderat and Schlinzig, 2011;Vicente and Reis, 2009;Watson et al, 2015), the CO group is generally quite a different group than the population reached by the conventional fixed-line survey, which is one of the major reasons that some researchers have called the validity and unbiasedness of the fixed-line telephone survey into question. It is therefore important to examine whether such uniqueness is also presented in our samples in the Hong Kong context.…”
Section: Comparison Of Socio-demographic Characteristics Among Different Types Of Respondentsmentioning
confidence: 99%
“…Many studies have found that demographics have an impact on mobile services usage (Watson, et al, 2015;Sillice, et al, 2018;Sarraute, et al, 2014). In the context of India, there are only 17.4% female mobile users (Rathee, 2018) and less than 25% of females have access to mobile phones (Barboni, et al, 2018) (GSMA, 2018.…”
Section: Comparative Analysis Of User Awareness Of Telecom Industry Across Different Demographicsmentioning
confidence: 99%